miR-744-5p Inhibits Non-Small Cell Lung Cancer Proliferation and Invasion by Directly Targeting PAX2 - Chen, Shaolin (Technol Cancer Res Treat, 2019)
Non-small cell lung cancer is one of the leading causes of cancer-related death worldwide. MicroRNAs have been characterized as critical regulators for cancer progression including non-small cell lung cancer. This work explored microRNA-744-5p expression in non-small cell lung cancer cell lines and normal cell line using quantitative real-time polymerase chain reaction. Connection of microRNA-744-5p and paired box 2 was analyzed with bioinformatic analysis, luciferase activity reporter assay, and Western blot. Effects of microRNA-744-5p or paired box 2 expression on non-small cell lung cancer cell behaviors were analyzed using a series of in vitro experiments. MicroRNA-744-5p was found to have decreased expression in non-small cell lung cancer cell lines compared with normal cell line. Paired box 2 was identified as a direct target for microRNA-744-5p in non-small cell lung cancer. Overexpression of microRNA-744-5p inhibits non-small cell lung cancer cell proliferation, colony formation, and cell invasion in vitro through targeting paired box 2. The present study provided novel insights into the biological functions of microRNA-744-5p in non-small cell lung cancer.